Sanitary inspection of animal products: discussing food quality in Brazil - Jacob, Michelle Cristine Medeiros; Azevedo, Elaine (Saúde e Sociedade, 2020)
In 2017, at Rock in Rio, Sanitary Surveillance seized more than 160 kg of animal products, including cheese and hand-crafted sausages, from a renowned Brazilian chef for lack of a federal sanitary inspection stamp. This event rekindled the debate on food quality in the country. In this paper, we discuss animal products’ inspection in Brazil and advocate for a broad concept of quality. Our method relays on Adorno’s essay proposal. We present the national scenario of the inspection, defining governmental responsibilities, conflicts of interest, and undergoing proposals to review current laws. Then we approach the expansion of the concept of food quality, contextualizing it in the contemporary movement called “quality turn”. Lastly, we indicate the challenges of the Brazilian political scenario and highlight the epistemological, political and ethical reforms needed for the debate on food quality to promote the Food and Nutrition Security of the Brazilian population.